Comparison of diagnostic accuracy of 3 diagnostic criteria combined with refined pathological scoring system for drug-induced liver injury. Issue 41 (9th October 2020) - Liu, Yiqi; Li, Ping; Wang, Fangfang; Liu, Liang; Zhang, Yilian; Liu, Yonggang; Shi, Ruifang
Abstract : Abstract: Drug-induced liver injury (DILI) is difficult in diagnose, criteria used now are mostly based on history review. We tried to evaluate the value of these criteria and histopathology features in DILI to perform a method diagnosing DILI more definitely. We enrolled 458 consecutive hospitalized DILI patients from January 1, 2012 to December 31, 2018, using Roussel-Uclaf Causality Assessment Method (RUCAM), Maria & Victorino scale (M&V), and Digestive Disease Week-Japan criterion (DDW-J) combined with refined pathological scoring system respectively to perform the evaluation. A total of 458 DILI patients were enrolled, the area under receiver operating characteristics (AUROC) of the 3 clinical diagnostic criteria were 0.730 (95% confidence interval [CI]: 0.667–0.793), 0.793 (95% CI: 0.740–0.847), and 0.764 (95% CI: 0.702–0.826) respectively. Three hundred two DILI patients' liver biopsies were included: steatosis in 204 cases (67.5%), cholestasis in 151 cases (50%), cell apoptosis in 139 cases (46%), eosinophil granulocyte infiltration in 131 cases (43.4%), central and/or portal phlebitis in 103 cases (34.1%), iron deposition in 90 cases (29.8%), and pigmented macrophages in 92 cases (30.5%). The AUROC of refined pathological scale combined with 3 criteria were 0.843 (95% CI: 0.747–0.914), 0.907 (95% CI: 0.822–0.960), and 0.881 (95% CI: 0.790–0.942) respectively. In hepatocellular type, the AUROCs were 0.894 (95% CI: 0.787–0.959), 0.960 (95% CI: 0.857–0.994), and 0.940 (95% CI: 0.847–0.985); in cholestatic type, the AUROCs were 0.750 (95% CI: 0.466–0.931), 0.500 (95% CI: 0.239–0.761), and 0.500 (95% CI: 0.239–0.761); in mixed type, the AUROCs were 0.786 (95% CI: 0.524–0.943), 0.869 (95% CI: 0.619–0.981), and 0.762 (95% CI: 0.498 to –0.930). Combined with pathological scale can significantly improve the accuracy of clinical diagnostic criteria, no matter in alone or combined condition, M&V might be more accurate in diagnosing DILI from suspected patients.